Underwater Shockwave Pretreatment Process to Improve the Scent of Extracted Citrus junos Tanaka (Yuzu) Juice - Eisuke Kuraya; Akiko Touyama; Shina Nakada; Osamu Higa; Shigeru Itoh (International Journal of Food Science)
Citrus junos Tanaka (yuzu) has a strong characteristic aroma and thus its juice is used in various Japanese foods. Herein, we evaluate the volatile compounds in yuzu juice to investigate whether underwater shockwave pretreatment affects its scent. A shockwave pretreatment at increased discharge and energy of 3.5 kV and 4.9 kJ, respectively, increased the content of aroma-active compounds. Moreover, the underwater shockwave pretreatment afforded an approximate tenfold increase in the scent intensity of yuzu juice cultivated in Rikuzentakata. The proposed treatment method exhibited reliable and good performance for the extraction of volatile and aroma-active compounds from the yuzu fruit. The broad applicability and high reliability of this technique for improving the scent of yuzu fruit juice were demonstrated, confirming its potential for application to a wide range of food extraction processes.